Improving the Estimation Methodology of Monthly Data in Direction of Trade Statistics - Gong, Xiaoning (Washington, D.C. : International Monetary Fund, 1994)
The quality of the estimated data in DOTS depends on the availability and accuracy of direction of trade reports and the estimation methodology. Because of the low coverage of monthly reporting, the estimating procedure plays a role of increased importance. This study, however, reveals two deficiencies in current DOTS estimation methodology: The information on total trade in IFS is not efficiently used, and the assumed uniform 10 percent CIF/FOB factor is inappropriate. Accuracy would be improved if IFS total trade were allocated, when available, according to the shares of total trade derived from partner data; and the uniform 10 percent CIF/FOB factors were replaced by adjustment factors derived from historical data.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United States